A proposed mechanism for texture proterty of woody breast in broilers - Welter, Amelia; Wu, Wan Jun; O'Quinn, Travis G.; Houser, Terry A.; Boyle, Elizabeth A.; Chao, Michael D.; Boyle, Daniel L.; Bowker, B.; Zhuang, H. (My University, 2019)
OBJECTIVE: Woody breast is a myopathy observed in chicken breast meat (Pectoralis major) characterized by its tough and rubbery texture. However, the exact causation of woody breast texture is still unknown. The objective of this preliminary study was to evaluate if the abnormal meat texture observed in woody breast meat is due to sarcoplasmic reticulum (SR) dysfunctionality due to rapid leakage of intracellular calcium. MATERIALS AND METHODS: Fourteen Ross line broiler breast fillets (7 severe woody breast and 7 normal) were collected at 3 h postmortem from a commercial processing plant in the southeast United States. The 7 woody breast samples exhibited moderate to severe white striping. Each sample was trimmed, weighed, vacuum packaged and frozen at -20°C at approximately 8 hrs. postmortem. One 1.9 cm strip across the cranial end of each fillet was fabricated and pulverized in liquid nitrogen to measure sarcomere length, calpain activity, proteolysis and collagen content. Purge was collected from each sample to evaluate protein and free calcium concentration. RESULTS: Woody breast fillets were heavier than normal breast fillets (522.9vs.446.9g; P<0.05). Woody breast samples tended to have shorter sarcomeres (1.70vs.2.02µm; P=0.0543) and less intact troponin-T (relative intact troponin-T band density: 49.98vs.56.97%; P=0.0515). All µ-calpain was completely autolyzed for both the woody breast and normal samples at 8 hrs. postmortem, so no µ-calpain band was detected through immunoblotting. In addition, the purge from woody breast samples also had higher levels of free calcium (6.2vs.4.2nmol calcium/mg protein; P<0.05). Lastly, there was more collagen present in the woody breast samples (3.89vs.2.08mg collagen/g muscle tissue; P<0.05). CONCLUSION: The results indicated that the cause of texture abnormality of woody breast may be the combined effects of more calcium being released from the SR early postmortem resulting in shorter sarcomere length and more collagen being deposited in the chicken breast meat.
Keywords: Spring 2019